Development Of W03-Tio2 Nanotube Arrays For Water Electrolysis - Lai, Chin Wei (2013)
Solar hydrogen generation from water electrolysis is a key target for the development of sustainable hydrogen economy for future energy system. The formation of self-organized Ti02 nanotubes without bundling is essential for high efficiency In photoelectrochemical (PEC) water electrolysis application. Comprehensive investigations on different parameters, such as composition of electrolyte, anodization time, anodization voltage, anodization temperature and heat treatment temperature were conducted in order to control the specific architecture of nanotubes.